The Effect of Formulation Type on the Release of Benzoyl Peroxide from Microsponges: Benzoyl peroxide release from microsponges - Nokhodchi, Ali; Jelveghari, Mitra; Siahi, Mohammad-Reza; Dastmalchi, Siavoosh (Iranian Journal of Pharmaceutical Sciences, 2005)
Benzoyl peroxide (BPO) is a first-line topical treatment in acne vulgaris, and it is superior to antibiotics, because the bacteria do not develop resistance to it. Skin irritation is a common side effect, and it has been shown that controlled release of BPO from a delivery system to the skin could reduce the side effects while reducing percutaneous absorption. Therefore, the purpose of the present investigation was to prepare suitable controlled release formulations for BPO. This study examined whether the type of topical formulation (cream, gel and lotion) can affect the release behavior of BPO from microsponges. Benzoyl peroxide microparticles were prepared using an emulsion solvent diffusion method by adding an organic internal phase containing benzoyl peroxide, ethyl cellulose and dichloromethane into a stirring aqueous phase containing polyvinyl alcohol. The loading capacity of the drug content and the mean particle size of microparticles were determined. BPO microparticles were then incorporated into various formulations (creams, gels and lotions) for release studies. The micrograph of microsponges showed that they were spherical in shape and contained pores. It was shown that the drug:polymer ratio, stirring rate, volume of the dispersed phase influenced the particle size and drug release behavior of the formed microsponges and that the presence of emulsifier was essential for microsponge formation. The results showed that, generally, an increase in the ratio of drug:polymer resulted in a reduction in the release rate of BPO from microsponges which was attributed to a decrease in internal porosity of the microsponges. The release data showed that the highest release rate was obtained from lotions containing BPO microparticles and the lowest was obtained from cream formulations.